Combinatory Flowcytometric Approach in Pediatric Acute Lymphoid Leukemia Identifies Surrogate Minimal Residual Disease Markers - Noreen Grace George; Bhavika Rishi; Sanghmitra Ray; Manpreet Kaur; Raj Kamal; Shikha Garg; Sumit Mehndiratta; Nidhi Chopra; Shamsuz Zaman; Amitabh Singh; Aroonima Misra (Diagnostics)
Background/Objectives: Minimal residual disease (MRD) refers to the resistant clonal population of leukemia cells that survive induction chemotherapy, serving as a critical indicator of treatment response in pediatric Acute Lymphoid Leukemia (ALL). While flow cytometry (FCM) and molecular methods are standard for MRD detection, novel leukemia-associated immunophenotype (LAIP) markers are needed when conventional markers are insufficient. Methods: MRD was assessed in 218 pediatric B-ALL patients using a combinatory approach of Different-from-Normal (DfN) and LAIP strategies. An eight-color flow cytometry panel included routine MRD markers (e.g., CD10, CD19, and CD20) and less commonly used markers (e.g., CD123, CD73, CD86). Cytogenetic and molecular profiling were integrated to evaluate the association between genetic abnormalities and MRD positivity. Results: The combined DfN and LAIP approach enhanced MRD detection sensitivity compared to individual methods. CD7 showed a significant association with MRD positivity (p = 0.003), whereas CD73 (p = 0.000) and CD86 (p = 0.002) correlated with MRD-negative status. CD123 exhibited the highest aberrancy among MRD-positive cases, while CD81 had the lowest. These findings highlight the prognostic potential of CD73 and CD86 for MRD-negative status, complementing the established utility of CD123. Conclusions: Incorporating novel markers (CD123, CD73, CD86, and CD81) into MRD panels enhances detection sensitivity and clinical applicability. These markers are compatible with standard flow cytometry, supporting their integration into routine practice for comprehensive MRD evaluation, ultimately improving therapeutic outcomes in pediatric B-ALL.